A práxis da ação comunicativa numa escola técnica: contribuições de Jürgen Habermas - Costa, Edilson da (2002)
The present research had the objective to check the possibility to apply the theory of Jürgen Habermas into the classroom. As a new parameter to technological education with this theory and trying to build the new curricular directions based upon the Communicative Action. This new parameter is linguistics. It presents the concepts of communicative action, the acts of speaking, the world of life and the system. It brings the educational practice related to the authors thoughts through concepts of education, technology, Technology of Education and Educational Technology. It doesn’t have the purpose to present a new pedagogical model, but provide “ways” to construct knowledge through interaction. It is a qualitative research as a case study. The results show that a practice based in a communicative action which privileges collective activities can facilitate the problem solving and also can generate new knowledge. In addiction, points to some contributions of Habermas’ theory to Technological Education showing that the citizen should be prepared to live the present reality: use the technology without being dominated by it.